RNA-Seq Analyses Reveal Roles of the HVCN1 Proton Channel in Cardiac pH Homeostasis - Wu, Xin; Li, Yawei; Maienschein-Cline, Mark; Feferman, Leonid; Wu, Longjun; Hong, Liang (Frontiers in Cell and Developmental Biology, 2022)
The voltage-gated proton channel HVCN1 is a member of the voltage-gated ion channel family. HVCN1 channel controls acid extrusion and regulates pH homeostasis in various cell types. Recent evidence indicated that the HVCN1 channel was associated with cardiac function. To investigate the role of HVCN1 in cardiac myocytes, we performed an RNA sequencing analysis of murine hearts and showed that HVCN1 null hearts exhibited a differential transcriptome profile compared with wild-type hearts. The RNA-seq data indicating impaired pH homeostasis in HVCN1 null hearts were the downregulated NADPH oxidoreductases (NOXs) and decreased expression of Cl-/HCO3- exchanger, indicating HVCN1 is a regulator of gene transcriptional networks controlling NOX signaling and CO2 homeostasis in the heart. Additionally, HVCN1 null hearts exhibited differential expression of cardiac ion channels, suggesting a potential role of HVCN1 in cardiac electrophysiological remodeling. The study highlights the importance of HVCN1 in cardiac function and may present a novel target associated with heart diseases.